(untitled) (Journal of Pathology of Nepal, 2023)
Starting rifampicin in patients with Addison’s disease or adrenal tuberculosis may precipitate an adrenal crisis as a result of the induction of CYP 3A4 which in turn leads to increased breakdown of cortisol. We report this rare phenomenon to increase awareness among healthcare professionals.